Analisis Pengembangan Sekolah Dasar Multiliterasi untuk Pendidikan Abad 21 - Kartika Sari, Erna; Abidin, Yunus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In the 21st century, education demands that students acquire a wide range of adaptable skills to navigate technological advancements and global challenges. Elementary schools, as the foundational stage of formal education, play a crucial role in fostering multiliteracy skills. These skills encompass digital, visual, environmental, financial, and cultural literacy. The goal of multiliteracy is not only to enhance cognitive abilities but also to develop students' character and social responsibility. This study aims to examine how multiliteracy is developed in elementary schools to prepare students for the demands of 21st-century education. The research employs the Systematic Literature Review (SLR) method, which involves gathering, evaluating, and analyzing pertinent literature on the development of multiliteracy in elementary education. The SLR process includes formulating research questions, selecting keywords, searching scientific databases, and choosing and analyzing studies based on specific criteria. The findings indicate that implementing multiliteracy in basic education positively impacts the development of critical, creative, and adaptive skills, as well as the shaping of students' character. However, challenges in implementing multiliteracy in Indonesia include limited resources and teacher preparedness, necessitating policy support and further training for effective implementation.